Iniciativas inovadoras que promovem acessibilidade - VIEIRA, Mayara de Oliveira (Universidade Federal do Pará, 2021)
This work is the result of an investigation into "Innovative initiatives that promote accessibility" and started from the following question: which innovative processes and/or products promote accessibility for people with disabilities within higher education? It has, as its methodological field, the method of cartography from the perspective of an intervention research in order to make visible subjective processes and monitor both objective and subjective processes. The study sought to investigate processes and/or products with the potential to promote communicational, architectural or instrumental and attitudinal accessibility, either by solving a problem or by a new approach. To this purpose, three research territories were chosen. In the first one, on Communication Accessibility, the "KitAcesso" was researched and produced, consisting of five applications, five info graphics, a workshop and an informative blog. The applications were selected through curatorship, specialized readings, supervised internship guidance and searches on websites supported by selection criteria. Info graphics were elaborated as a form of documentation. For the production of the research data, a workshop was held on the processes developed and, finally, the creation of a blog to disseminate of the kit. The second territory, on Accessibility with Rapid Prototyping, there was also the process of research and production of "KitAccessSol" compounded by the solution of two accessibility problems. The first one on architectural and instrumental accessibility through the design, model and 3D printing of a keyboard adapted for people with low vision. The second one on architectural accessibility through the design and model of a mobile ramp access to the drinking fountain of the postgraduate building in the Instituto de Tecnologia da UFPA. The kit also includes a on the adapted keyboard construction process. These problems were investigated during a curatorship of projects, programs and products on free websites on rapid prototyping and during a survey in the accessibility coordination of UFPA. To the third territory, on Attitudinal Accessibility by Art, the film "The Shape of Water" was chosen to reflect on attitudinal accessibility seeking to understand how film language can reinforce stereotypes, myths and prejudices that were historically and culturally built, as well as in order to contribute to dialogue on inclusion. The cartography from these territories went the long way along both the elaboration of laws that ensure rights of people with disabilities and in the construction of processes and/or products that promote accessibility, particularly in higher education, with an approach that sought to be broad, but considering important particularities. There is a great lack of knowledge about applications that help people with disabilities and it is necessary to promote digital literacy on accessibility at the university. Despite technological advances, the 3D printer is still little used at the university level as a tool to promote accessibility, a few simple and low cost projects in Assistive Technology are implemented and there is a lack of trained professionals in this area. As for attitudinal accessibility, there is a great silence that needs to be broken, we believe that Art is a promising way as it approaches sensitivity to promote encounters, which can mean the changes we have dreamed of and a more inclusive society.